Some unnecessary or inadequate common practices in regulated LC–MS bioanalysis. (October 2014) - Tan, Aimin; Awaiye, Kayode; Trabelsi, Fethi
The global bioanalytical community increasingly craves scientifically sound practices and guidance where the rationale is given for each requirement. To this end, it is critical to first evaluate all the existing practices and requirements based on scientific findings and critical thinking. Here we are challenging several important common practices in regulated LC–MS bioanalysis, from the requirement of at least six different calibration concentrations, no extrapolation, use of blank and zero standard in each batch, selection of quality controls, to the way matrix effect and dilution integrity are being validated. Both the reasons why these common practices are unnecessary or inadequate and the potential solutions are presented.